Growth Performance and Leaf Nutrient Status of Aonla (Emblica officinalis Gaertn) Cultivars in Saline and Sodic Soils - Shukla, S K; Pathak, R K (Annals of Arid Zone, 2016)
An experiment was conducted to evaluate the performance of aonla cultivars. viz., Banarasi, Francis, Krishna and Kanchan in artilicially developed saline and sadie soils. Data recorded on plant survival. growth and leaf nutrient status revealed 100% plant survival in Francis andÂ· Kanchan in both saline and sodie soils. Growth of aonla cultivars. viz., Francis and Kanchan. was significantly better than that in Banarasi and Krishna. Total nitrogen. phosphorus and potassium status in the leaves of all aonla cultivars decreased significantly both in saline and sodic soils. Calcium and magnesium contents were reduced in response to sodicity. whereas salinity caused marked increase in the status of these two nutrients in all the aonla cultivars. Leaf sodium accumulation was in toxie quantities in response to both salinity and sodicity (alkalinity). Leaf injury symptoms were more conspicuous in Banarasi and Krishna than in Francis and Kanchan.